2015
DOI: 10.1007/s00221-015-4269-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia exacerbates cerebral injury through oxidative stress, inflammation and neuronal apoptosis in MCAO/reperfusion rats

Abstract: Recent studies showed that hyperglycemia enhanced brain damage when subjected to transient cerebral ischemic stroke. However, the etiologic link between them has been less known. In the present study, based on an experimental rat's model of hyperlipidemia combined with cerebral ischemia-reperfusion injury (I/R), we herein showed that hyperlipidemia induced by high-fat diet (HFD) resulted in considerable increase in serum triglycerides, cholesterol and low-density lipoprotein cholesterol, and remarkable decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…In this situation which is defined as hypoxia, the brain cells loss their normal functionalities and metabolism (37)(38)(39). The presence of abundant polyunsaturated fatty acids (40) and lower levels of antioxidant enzymes such as catalase and glutathione peroxidase in brain cells, makes them vulnerable and sensitive to free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation which is defined as hypoxia, the brain cells loss their normal functionalities and metabolism (37)(38)(39). The presence of abundant polyunsaturated fatty acids (40) and lower levels of antioxidant enzymes such as catalase and glutathione peroxidase in brain cells, makes them vulnerable and sensitive to free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…57 Worse stroke outcome has also been confirmed in diet-induced models in which animals become obese due to being fed a high-fat diet. These detrimental effects of a high-fat diet have been observed in rat, 58,61,65,73,82,93 mouse 60,64,66,88 and gerbil 62,63,94 models of diet-induced obesity. A variety of models of cerebral ischaemia have also been used in these studies, including transient and permanent occlusion of the middle cerebral artery, common carotid artery ligation and exposure to a low-oxygen environment.…”
Section: Experimental Stroke In Obese Rodentsmentioning
confidence: 99%
“…Hyperlipidemia was also linked to brain CYP modifications. It has been shown that induction of CYP2E1 in the brain occurs in hyperlipidemia subjects, or after associated ischemia-reperfusion (IR) injury [92]. Furthermore, CYP2E1 induction can contribute to the production of tissue-damaging radicals, inflammatory response, and neuronal apoptosis.…”
Section: Additional Factors Influencing P450 Function In the Brainmentioning
confidence: 99%
“…Furthermore, CYP2E1 induction can contribute to the production of tissue-damaging radicals, inflammatory response, and neuronal apoptosis. Therefore, the occurrence of hyperlipidemia in patients with cerebral ischemia presents a higher threat to neuronal degeneration, because of CYP2E1 expression [92]. …”
Section: Additional Factors Influencing P450 Function In the Brainmentioning
confidence: 99%